Comparative Analysis of Clinical Effects of Mineral Trioxide Aggregate in the Treatment of Endodontic Diseases - Jian SUN; Yuanyuan WEI; Xiaobei TIAN; Qinglin MEN (Tehran University of Medical Sciences, 2019)
Background: We aimed to evaluate the efficacy of mineral trioxide aggregate (MTA) in the treatment of endodontic disease. Methods: Oversell, 384 patients with endodontic disease treated in Xuzhou Stomatological Hospital, Xuzhou, China, from June 2015 to June 2017 were selected, and randomly divided into four groups with 96 cases per group. The repair effects of MTA, zinc phosphate cement (ZPC), silver amalgam and light-curing calcium hydroxide (LCH) on the teeth and dental pulp of patients in the four groups were compared. Meanwhile, the ill symptoms of the patients were observed to confirm whether they could be alleviated. Besides, whether the repair effects were related to ages of patients, perforation diameters of diseased teeth and repair materials was discussed. Results: The success rates of MTA group, ZPC group, LCH group and silver amalgam group were 90.6%, 68.7%, 70.8% and 52.1%, respectively. The success rate of MTA group was significantly higher than that of ZPC group, silver amalgam group and LCH group. When the success rates of four groups were compared, the differences were statistically significant (P=0.0072). The patient's age, repair material and perforation diameter were positively correlated with MTA repair effect (P=0.003, P=0.002, P=0.01). The patients' teeth in each group were repaired with different materials, and the reexamination was conducted 4 weeks later. Three patients in the silver amalgam group were found to have gingival swelling. Conclusion: The therapeutic effect of MTA was significant in the treatment of endodontic disease, and it is worthy of clinical application.